(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
Environmental pollution through plastics is increasing due to the speedy global progress that often prioritises human wishes over universal health. Despite worldwide efforts to mitigate legacy contaminants and pollutants, the continuous introduction of new substances remains a major threat to both people and the planet. In response, these worldwide initiatives, which focus on risk evaluation and assessment with the regulation of these emerging contaminants, were established. The key focus of this chapter is to provide data and information on the chemistry of analysis and determination of microplastics and nanoplastics in the environment. Information and data were sourced from published databases such as Scopus link, PubMed link, Royal Society of Chemistry Publishing link, SpringerLink, Google Scholar link, Magiran link, and Taylor and Francis Online link using the keywords microplastic and nanoplastic. The study revealed that there are several techniques for the determination and analysis of microplastics and nanoplastics. The techniques are particle-based methods for non-destructive (thermal degradation) and non-destructive spectroscopic methods (scanning probe microscopy coupled to spectroscopy and Raman-based analysis of nanoplastics enabled by optical tweezers). It was concluded that all these techniques can be used to gain information about various plastic particle properties